Optimalisasi Pemanfaatan Media Pembelajaran Berbasis TIK Melalui Program Kampus Mengajar bagi Sekolah Terpencil di Kabupaten Lebak - Rida Oktorida Khastini; Nani Maryani; Dinar Sugiana; Akhmad Baihaqi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service activity aims to optimize the use of information and communication technology (ICT)-based learning media through campus teaching programs to improve the quality of education in remote areas. The method of implementing this service is with training which includes the stages of preparation, implementation, and evaluation of results through filling out questionnaires by teachers and students. This service partner is SMAN 1 Malingping as one of the remote school areas in Lebak district. The results of this dedication show that partners, namely teachers and students, feel the positive impact of using ICT application-based learning media in the classroom. Teachers' skills in implementing ICT-based learning media and students' motivation to learn increases. In addition, teachers have succeeded in overcoming various challenges in the learning process by optimizing the use of ICT-based learning media.